Applying a dissident's stance on recent trends in urban research - quantitative methods as a symptom of growing marketing pressures on the city - Firley, Eric (ARCC Conference Repository, 2014)
The paper investigates the rapidly increasing use of data in urban research, questioning cause and effect in order to understand how the usually publicized reasons for this trend - scientific progress and ecological threats - relate to wider economic interests as the actual underlying forces of transformation. Dealing in essence with a whole discipline within the philosophy of science - the relation between scientific progress, human behavior and the economic realm - the author does not endeavor to bring new findings to the philosophical discussion as such, but applies elements of it to the urban realm. Just like the fast development of mobile devices - as one example among many others - can not simply be attributed to technological progress, but also to the market's fervent demand and the product's considerable profitability, the author argues that the impressive change of paradigm in urban research might as well be motivated by something else than simple pragmatic needs and a new fashion for computation. He also observes the dissolution of a formerly existing discussion between experts towards a situation in which the wider public is addressed as the consumer of a product that is defined by an oligopoly of public-private interests. The character of this marriage leads for the urban professional to a new method of not only approaching, but also perceiving and "selling” the urban realm, one example being different types of city rankings that are using figure-based information in order to attract investment through the creation of an image. This duality and tension, between the rationality of a figure-based approach and the marketing pressure that consists in provoking irrational buying decisions, crystallizes as one ofthe study's major outcomes. Is what we see just the agreeable tip of a manipulative iceberg? How can the urban designer adjust to these trends, avoiding to be used as a mere tool for empty marketing campaigns?